Reevesioside A, a cardenolide glycoside, induces anticancer activity against human hormone-refractory prostate cancers through suppression of c-myc expression and induction of G1 arrest of the cell cycle. - Wohn-Jenn Leu; Hsun-Shuo Chang; She-Hung Chan; Jui-Ling Hsu; Chia-Chun Yu; Lih-Ching Hsu; Ih-Sheng Chen; Jih-Hwa Guh (PLoS ONE, 2014)
In the past decade, there has been a profound increase in the number of studies revealing that cardenolide glycosides display inhibitory activity on the growth of human cancer cells. The use of potential cardenolide glycosides may be a worthwhile approach in anticancer research. Reevesioside A, a cardenolide glycoside isolated from the root of Reevesia formosana, displayed potent anti-proliferative activity against human hormone-refractory prostate cancers. A good correlation (r² = 0.98) between the expression of Na⁺/K⁺-ATPase α₃ subunit and anti-proliferative activity suggested the critical role of the α₃ subunit. Reevesioside A induced G1 arrest of the cell cycle and subsequent apoptosis in a thymidine block-mediated synchronization model. The data were supported by the down-regulation of several related cell cycle regulators, including cyclin D1, cyclin E and CDC25A. Reevesioside A also caused a profound decrease of RB phosphorylation, leading to an increased association between RB and E2F1 and the subsequent suppression of E2F1 activity. The protein and mRNA levels of c-myc, which can activate expression of many downstream cell cycle regulators, were dramatically inhibited by reevesioside A. Transient transfection of c-myc inhibited the down-regulation of both cyclin D1 and cyclin E protein expression to reevesioside A action, suggesting that c-myc functioned as an upstream regulator. Flow cytometric analysis of JC-1 staining demonstrated that reevesioside A also induced the significant loss of mitochondrial membrane potential. In summary, the data suggest that reevesioside A inhibits c-myc expression and down-regulates the expression of CDC25A, cyclin D1 and cyclin E, leading to a profound decrease of RB phosphorylation. G1 arrest is, therefore, induced through E2F1 suppression. Consequently, reevesioside A causes mitochondrial damage and an ultimate apoptosis in human hormone-refractory prostate cancer cells.